Efektivitas E-Modul Berbasis SDGs dengan Pendekatan STEM untuk Meningkatkan Kreativitas dan Hasil Belajar Peserta Didik SMA di Samarinda - Sabina, Siti; Nasution, Ruqoyyah; Maasawet, Elsje Theodora; Masitah, Masitah (Biocaster : Jurnal Kajian Biologi, 2025)
The STEM (Science, Technology, Engineering, and Mathematics) approach is a learning method that integrates four fields of science to encourage problem-solving and creative thinking in a contextual manner. This study aims to test the effectiveness of Sustainable Development Goals (SDGs-based) E-Modules with a STEM approach in increasing students' creativity and learning outcomes on the Role of Fungi in Life material. The research used the true experiment method with a pretest-posttest control group design, involving students of class X of SMA Negeri 9 Samarinda which was divided into experimental classes and control classes. The instruments used are learning outcome tests and creativity assessment sheets that have been validated by experts. Data analysis was carried out with an independent sample t-test to test the significance of differences between classes, as well as N-Gain calculation to measure learning effectiveness. The results showed that the improvement in learning outcomes in the experimental class was relatively high with an N-Gain value of 0.73, while the control class was in the medium category with an N-Gain value of 0.42. The increase in creativity in the experimental class was also significant, especially in the aspects of flexibility and elaboration. The high category in the experimental class is achieved because the E-Module allows for self-exploration, project-based activities, as well as the relevance of the material to real life. In contrast, learning in the control class tended to be less stimulating to creative and reflective thinking skills. Thus, SDGs-based E-Modules with a STEM approach have proven to be effective in increasing students' creativity and learning outcomes, as well as supporting the development of 21st century skills.